Impact Achieving of Requirements Hedge Accounting on Accounting Information Systems Fundamental Qualities in Companies Iraq - Assistant Professor, Emad Al-Harash (European Science Publishing, 2024)
The current study looked at how meeting standards for hedge accounting affected the core characteristics of accounting information systems, which in turn affected the performance of businesses listed on the Iraqi stock exchange. A number of requirements were measured using hedge accounting, such as the measurement of financial instruments at fair value or expired cost, the classification of financial instruments at affair value, the cancellation of the available-for-sale investment classification, the restrictions on reclassifying financial assets, the treatment of gains or losses from unclassified equity instruments for trading in comprehensive income and continuing from year to year, and the linking of the company's financial asset and liability classification to its business model rather than management decision. Relevance, dependability, and comparability of accounting information were utilised to gauge the core attributes of the accounting information system. According to the findings, the companies listed on the Iraqi stock exchange comply with the requirements of hedge accounting, indicating that they understand these requirements and how they can impact the accounting relevance, accounting reliability, and accounting comparability of the accounting data that accounting information systems submit.
Keywords: Hedge Accounting; Accounting Information Systems, Fundamental Qualities, Companies, and Iraq.